Kajian Biaya Premi Pengutipan Lateks dan Lump Pada Topografi Datar dan Berbukit Di Kebun Gunung Para PT. Perkebunan Nusantara III - Lubis, Fadli Akbar; Marzuti Isra; Purjianto; Bintang Eka Utama (Agro Estate, 2024)
The productivity of rubber plants in the company is not only influenced by technical factors but is also influenced by the flat and hilly topography of the plantation land. This difference in topographic conditions affects basic number of tasks in latex and lump filling process. This research aims to determine costs incurred by companies to pay premium costs for quoting latex and lumps on flat and hilly topography. This research was carried out at Gunung Para Plantation, PT. Perkebunan Nusantara III, Serdang Bedagai, North Sumatra. The method used in this research is decriptive analysis method. The data taken in this research is primary and secondary data. Direct observations were carried out to obtain general information about the Gunung Para Plantation, as well as conducting interviews with Assistant Afdeling V. from the information resulting from this research in can be concluded that at the Gunung Para Plantation, PT. Perkebunan Nusantara III incentive rates for tappers on flat topography are same as those for tappers on hilly topography, however duty base for tappers on hilly topography is low than the normal duty base because topography has a higher risk than on flat topography areas. The research results show that in May - June 2022 there will be an increase in premium payment costs of 214% in flat topographic land areas, and in hilly topographic land areas there will be an increase of 80%. Results of this research emphasize importance of budget planning for financing latex and lump incentives to improve company performance